Theological belief towards Islamic spiritual belief: Evidence from South Sulawesi, Indonesia - Ruslan, Ruslan (HTS teologiese studies, 2022)
Indonesia has the biggest Muslim population globally, and one of the Islamic beliefs among people of this nation is tarekat, which is sometimes considered as a heretic. Therefore, this article aims to analyse the meaning of diction tarekat according to the Qur’an and its implications for the Buginese community, one of the oldest ethnicities in Indonesia. This is a conceptual and empirical research with the purposive sampling method used to determine the informants from several tarekat leaders and congregations. Data were collected through documentation, observation and interviews and analysed using Miles and Huberman’s qualitative analysis technique. This process consists of data reduction, display and drawing conclusions. The study results showed that, firstly, the word tarekat in the Qur’an indicates the meaning of inner journey and the methods and ways of thinking, acting and behaving. Secondly, to the Buginese community, it implies a spiritual path to a higher level of appreciation towards their God. Thirdly, the meaning of the diction tarekat in the Qur’an has implications for its understanding, which can be seen in the practice of dhikr, spiritual behaviour and the way of life of those implementing these heretics.Contribution: This article enriched the religious belief among Muslims, which scholars rarely uncover. Adherents of Islam in Indonesia have a social and political responsibility regarding religious tolerance within and outside other religions. This proves that Muslims contribute to world peace in Middle-East and South-Eastern Asia.